Corpies: Bisnis Kreatif Pemanfaatan Sampah Kaleng dan Kertas Menggunakan Teknik Lukis Sebagai Usaha Meningkatkan Nilai Benda Bekas Pakai - Joni Agung Sudarmanto (Universitas Negeri Malang, 2021)
Abstract: In this modern era, handmade products are increasingly popular because people have begun to appreciate art. SMEs have many ways to grow with many government facilities and exhibitions that support handmade products. This is a positive sign for domestic products to be more prominent. Products that raise social issues also get more attention from the public, one of which is environmental issues. Behind the consumptive culture of humans, there are problems that they create, one of the most visible is the amount of waste. To overcome this problem, innovations were created to process consumption waste into usable products that have more economic value than just being recycled.